2016
DOI: 10.1142/s021827181650084x
|View full text |Cite
|
Sign up to set email alerts
|

Black holes with scalar hair in Einstein–Gauss–Bonnet gravity

Abstract: The Einstein-Gauss-Bonnet gravity in five dimensions is extended by scalar fields and the corresponding equations are reduced to a system of non-linear differential equations. A large family of regular solutions of these equations is shown to exist. Generically, these solutions are spinning black holes with scalar hairs. They can be characterized (but not uniquely) by an horizon and an angular velocity on this horizon. Taking particular limits the black holes approach boson star or become extremal, in any case… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Finally, it would be interesting to construct rotating solutions, and see how the solutions presented here connect to those studied in [12].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Finally, it would be interesting to construct rotating solutions, and see how the solutions presented here connect to those studied in [12].…”
Section: Discussionmentioning
confidence: 92%
“…An interesting feature about five dimensional gravity is that Gauss-Bonnet term becomes dynamically non-trivial. The effect of the Gauss-Bonnet deformation to Myers-Perry hairy black holes was studied in [12].…”
mentioning
confidence: 99%
“…It will be continued by extending the investigations on teleparallel Gauss-Bonnet scalar-torsion theory, such as the theories discussed in [65][66][67]. In the Riemannian case, it is well known that these theories have asymptotically flat scalarized black holes with spontaneous scalarization [32,33,36]. Since the Gauss-Bonnet scalar-torsion theories contains the standard Riemannian case in a certain limit, it is obvious to mention that those theories also will contain those solutions.…”
Section: Discussionmentioning
confidence: 94%
“…In these theories, it was shown that scalarised black holes exists for several choices of the non-minimal coupling function F (ψ) [30][31][32][33][34][35][36]. The first example was provided in [30,31] assuming a linear coupling (F (ψ) ∝ ψ).…”
Section: Introductionmentioning
confidence: 99%
“…Note that in the later case, again a complex doublet of scalar fields has been used. Rotating EGB black holes with uncharged scalar hair were shown to exist in [62]. An interesting new feature appearing in 5-dimensional EGB gravity is that now static, electrically charged black hole solutions with charged scalar hair (that possesses harmonic time-dependence) do exist [63].…”
Section: Introductionmentioning
confidence: 99%